THE IMPACT OF MOTIVATION AND WORK DISCIPLINE ON CV EMPLOYEE PERFORMANCE. BUMI ANGKASA SEJAHTERA PALEMBANG - Dita Marisa Putri; Syahyuni; Syaiful Sahri (Fakultas Ekonomi Universitas Tridinanti Palembang, 2023)
The purpose of this study is to analyze the effect of motivation and work discipline on the performance of CV employees. bumi angkasa sejahtera Palembang partially and simultaneously. The results of this study are Motivation and work discipline simultaneously affect the performance of CV employees. Bumi Angkasa Sejahtera Palembang which is shown by the F value count 13.820 which is greater than F table 3.17, then with a significance level of 0.000 smaller than the alpha probability level of 0.05, which means the null hypothesis (Ho) is rejected and the alternative hypothesis (Ha) is accepted, then motivation and work discipline have a significant effect on the performance of CV employees. Bumi Angkasa Sejahtera Palembang. Partially, Employee motivation CV. Bumi Angkasa Sejahtera Palembang has a positive and significant effect on employee performance as shown from the results of a multiple linear regression coefficient of 0.420 with a significance level of 0.001. Meanwhile, the work discipline of CV employees. Bumi Angkasa Sejahtera Palembang has a positive and significant effect on employee performance as shown by the results of a multiple linear regression coefficient of 0.273 with a significance level of 0.02.